Exercise systolic blood pressures are of questionable value in the assessment of the adult with a previous coarctation repair. Issue 2 (1st February 2003) - Swan, L; Goyal, S; Hsia, C; Hechter, S; Webb, G; Gatzoulis, M A
Abstract : Background: The role of exercise testing in the follow up of adults with a coarctation repair is unclear. Exercise induced systolic hypertension has been advocated as an indication for further investigation; however, the value of exercise testing in this role has been questioned, especially in paediatric populations. Objective: To assess the value of resting and exercise blood pressure measurements in a cohort of adults with repaired coarctation. Setting: Tertiary referral centre for adult congenital cardiac disease. Patients: 56 patients (33 male, 23 female) with a previous coarctation repair, and 33 age matched controls. Main outcome measures: Resting and exercise blood pressures, including arm–leg systolic blood pressure gradients; standard echocardiographic measurements of left ventricular mass, aortic root diameter, and repair site gradient. Results: The coarctation cohort had higher resting upper limb blood pressures than the controls (systolic: 129.7 v 120.7 mm Hg, p = 0.014; diastolic: 76.8 v 72.2 mm Hg, p = 0.02). Mean resting arm–leg systolic blood pressure gradient was also higher, at 3.6 v −2.2 mm Hg, p = 0.027. However, there were no differences between the peak exercise systolic blood pressures of the two groups. Peak exercise systolic blood pressure did not correlate with resting arm–leg blood pressure gradient ( r = 0.24, p = 0.13) or with repair site gradient ( r = 0.14, p = 0.39). Resting upper limb systolic blood pressure and resting arm–leg systolic blood pressure gradient were related to repair site gradient ( r = 0.33, p = 0.03, and r = 0.47, p = 0.002). Conclusions: Measurements of upper limb blood pressure during exercise are of limited value in the assessment of the post-repair coarctation patient. If routine exercise testing is to be advocated in this population it must be for another indication.